PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD N 005 SUNGAI PINANG KECAMATAN KUBU KABUPATEN ROKAN HILIR - Daud, Damanhuri Daud Damanhuri; ', Yurneli; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The background of this research is the process of learning and teaching classes IV SDN 005 Sungai Pinang Kecamatan Kubu Kabupaten Rokan Hilir on subjects IPA which is still dominated by the teacher so that students become passive, as well as material provided by the teacher and the learning outcomes are not satisfactory with an average value below the KKM. This study aims to determine there or not the effect of cooperative learning model TSTS both individually and classical toward student learning outcomes IV on the subject IPA SD N 005 Sungai Pinang Kecamatan Kubu Kabupaten Rokan Hilir. This study was conducted on 20 students. Data were collected through observation using observation sheet fot the data type of cooperative learning model two stay two stray (TSTS) through UAS I and UAS II for learning outcomes data, the results of the students increased in the first cycle compared to prior to the action or before PTK, as for the improvement of learning outcomes that occurred from before held PTK and after the cycle I an increase of 20%, in cycle I the students who completed as many as 12 people with 60% completeness. While on cycle II an increase of 35% with the thoroughness of the students were 19 people with a completeness of 95%. So there is difference between the increase in the cycle I and cycle II of 35%. While the activities of the students at the first meeting of the cycle I was 54.16%. The second meeting was 70.83%, for the second meeting was 95,83%. So between the cycle I and cycle II an increase of 25%. From the research and discussion as it has been described above that with use of cooperative learning model TSTS coorectly then the activity and student learning outcomes be improved and better. Key Words : Cooperative Learning Model Two Stay Two Stray (TSTS), IPA Learning Outcomes.